TARI SARAMA BABIAT TINJAUAN TERHADAP BENTUK - CHIKA KARTIKA PUTRI (Gesture: Jurnal Seni Tari, 2013)
Sarama Babiat Review Of The Dance Form. The purpose of this research is to discuss about the origin of the story, the content and form of the dance Sarama Babiat. To discuss this research uses theories that deal with topics such as the theory of forms, dance theory, theories of choreography, dance Babiat Sarama sense, understanding its origins and understanding acoustics. The research carried out for 2 months that is December 2013 until February 2014. The location of the research done at the Art Group Kulabu Pakantan Mountain Tapsel Madina-Medan. The methods used to discuss Babiat Sarama dance forms using qualitative descriptive method. The population in this research as well as a sample of interviewees, dancers, cultural figures and artists community know about the shape of the dance Sarama Babiat. Data collection techniques include the study of librarianship, observation, interview and documentation. Based on the research conducted, parsable forms of dance that consisted of 3 Babiat Sarama scene that should buffet, namely marsantabi, manombak and bala, manulak. Movement in the dance movements are Babiat Sarama spontaneity or improvisation, but bound by the 3 scene. Babiat Sarama dance in every scene has different properties. The nature of marsantabi is polite. The nature of the sacred is bala manulak whereas the nature of manombak is angry. Marsantabi scene wouldn't have a background member of respect to their ancestors. The scene has a background bala manulak Keywords: Dance, Dance Forms Babiat Sarama